The Dead Sea Scrolls translated : the Qumran texts in English - Garcia Martinez, Florentino (Grand Rapids: William B. Eerdmans : Leiden; New York: E.J. Brill, 1996)
Translation of: Textos de Qumran.
Includes bibliographical references